Effects of metformin plus myo-inositol compared to metformin alone as pre-treatment of ovulation induction in polycystic ovary syndrome with insulin resistance - Rani, Chalontika; Deeba, Farzana; Ishrat, Shakeela; Banu, Jesmine; Jahan, Shirin; Nazneen, Sohely; Akter, Sumaiya; Chowdhury, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder affecting reproductive-age women. Insulin resistance (IR) is a common disorder, which may impair female fertility by causing ovulatory dysfunction. Lifestyle modification and insulin sensitizers are commonly used in the management of IR. This study aimed to compare the effects of metformin plus myo-inositol versus metformin alone as pre-treatment in ovulation induction in polycystic ovary syndrome with insulin resistance. Methods: This prospective quasi-experimental study was conducted in the department of reproductive endocrinology and infertility, Bangabandhu Sheikh Mujib Medical University, Dhaka, from July 2020 to June 2021. A total of 52 insulin-resistant infertile PCOS women were included in this study, who were allocated into two groups by using odd-even numbers and given two different treatments. Results: Mature follicles and mid-luteal serum progesterone levels were significantly higher in metformin plus myo-inositol group (60.9% versus 28.0% and (73.9% versus 44.0%) respectively. The ovulation rate was significantly higher in metformin plus myo-inositol group (73.9% versus 44.0%), and the pregnancy rate was higher in metformin plus myo-inositol group (26.92% versus 11.54%), but the difference was not statistically significant. Conclusions: Ovulation rate was significantly higher in metformin plus myo-inositol group than metformin alone group. The pregnancy rate was higher in metformin plus myo-inositol group but no significant difference was found between the two groups.